2021
DOI: 10.3390/jcm10010136
|View full text |Cite
|
Sign up to set email alerts
|

A Psychosocial Genomics Pilot Study in Oncology for Verifying Clinical, Inflammatory and Psychological Effects of Mind-Body Transformations-Therapy (MBT-T) in Breast Cancer Patients: Preliminary Results

Abstract: Several studies have highlighted the key role of chronic inflammation in breast cancer development, progression, metastasis, and therapeutic outcome. These processes are mediated through a variety of cytokines and hormones that exert their biological actions either locally or distantly via systemic circulation. Recent findings suggest that positive psychosocial experiences, including psychotherapeutic interventions and therapeutic mind-body protocols, can modulate the inflammatory response by reducing the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…The Brain Wave Modulation Technique (BWM‐T; Celia & Cozzolino, 2021 ; Cozzolino & Celia, 2016 ; Cozzolino et al., 2021 ; Hirai, 1975 ) is a mind‐body intervention that combines mind‐body procedures with a neuroscientific perspective (Cozzolino & Celia, 2016 , 2021 ; Cozzolino et al., 2020 ; Cozzolino, Cocco, et al., 2021 ). The technique derives from studies on sleep conducted in the 1970s (Hirai, 1975 ; Hirai et al., 1968 , 1969 ; Kasamatsu & Hirai, 1973 ), which demonstrated the beneficial effects of a Zen meditation practice (the Zazen practice) in reducing EEG patterns and changing people's mental states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brain Wave Modulation Technique (BWM‐T; Celia & Cozzolino, 2021 ; Cozzolino & Celia, 2016 ; Cozzolino et al., 2021 ; Hirai, 1975 ) is a mind‐body intervention that combines mind‐body procedures with a neuroscientific perspective (Cozzolino & Celia, 2016 , 2021 ; Cozzolino et al., 2020 ; Cozzolino, Cocco, et al., 2021 ). The technique derives from studies on sleep conducted in the 1970s (Hirai, 1975 ; Hirai et al., 1968 , 1969 ; Kasamatsu & Hirai, 1973 ), which demonstrated the beneficial effects of a Zen meditation practice (the Zazen practice) in reducing EEG patterns and changing people's mental states.…”
Section: Introductionmentioning
confidence: 99%
“…This intervention was based on a mind‐body technique called the Brain Wave Modulation Technique (BWM‐T; Celia & Cozzolino, 2021 ; Cozzolino & Celia, 2016 ; Cozzolino, Vivo, et al., 2020 ) that has shown to be particularly helpful in reducing stress, anxiety and negative affect, while improving positive affect and well‐being (e.g. Celia, 2020 ; Cozzolino, Cocco, et al., 2021 ; Cozzolino et al., 2017 ; Rossi et al., 2011 ). Previous studies had suggested that it would be efficacious in a university population (Cozzolino, Celia, et al., 2021 ; Cozzolino, Girelli, et al., 2020 ; Cozzolino, Vivo, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria were as follows (1): female sex (2); cytologically or histologically confirmed MBC (3); HR+ disease defined as ER-positive and/or PR-positive (4); HER-2-disease according to an immunohistochemical score of 0, 1+ or 2+ but a negative fluorescence in FISH result (5); at least 4 hospital admissions records; and (6) received first-line therapy between January 2013 and June 2017. Patients who did not receive treatment or had other primary malignancies during observation were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…The marginal mandibular branches of the facial nerves are extremely special in nature. Once an injury occurs, the complications will be devastating and functions will be lost, which will involve the patient's facial aesthetics [9][10][11], causing great psychological trauma to the patient, and thus affecting tumor treatment [12,13]. Whether it is necessary to dissect the marginal mandibular branches of the facial nerves when removing the submandibular glands during comprehensive cervical lymphadenectomy, and whether the dissection can protect the marginal mandibular branches of the facial nerves are a subject worthy of clinical research.…”
Section: Introductionmentioning
confidence: 99%